Effect of Draw Solution on the Treatment of Humic Acid in Forward Osmosis Process - Mazrul Nizam, Abu Seman; Ryan Yeo, Whye Seong (2014)
This paper presents the effect of draw solution in forward osmosis process for the treatment of synthetic river water. Forward osmosis is a process which depends on the concentration gradient and also osmotic potential to treat water. In conjunction to that, the main factor which affects the entire process of forward osmosis is the draw solution as draw solution acts as the driving force which drives water to pass through semi-permeable membrane by means of concentration gradient. The draw solutions studied in this paper include calcium chloride, calcium nitrate, sodium chloride and fructose. Polyamide coated ultrafiltration membrane was used and different concentrations of draw solutions were used to treat synthetic river water which consists of 15mg/L of humic acid. Time was taken for a fixed volume of water and humic acid concentration at draw solution side was measured using uv-vis spectrometer to calculate the flux and also humic acid rejection respectively. The draw solution with the highest water flux is calcium nitrate with the reading of 2.7 x 10^-4 m3/m2.s at 1mol/L, whereas the lowest flux obtained is by fructose with the reading of 2.529 x 10^-05 m3/m2.s. Whereas for humic acid rejection, it was found to be high at every concentration of draw solultions at approximately 99%. Results from this work may be useful for treating river water by using forward osmosis with the most suitable draw solution.